1998
DOI: 10.1021/es980091o
|View full text |Cite
|
Sign up to set email alerts
|

Triphasic Desorption of Highly Resistant Chlorobenzenes, Polychlorinated Biphenyls, and Polycyclic Aromatic Hydrocarbons in Field Contaminated Sediment

Abstract: Pollutants in aged field sediments seem to differ from spiked sediments in their chemical and biological availability. Biphasic desorption is often used as an explanation. In the present study, desorption kinetics and partitioning of chlorobenzenes (CBs), polychlorinated biphenyls (PCBs), and polycyclic aromatic hydrocarbons (PAHs) in long term field contaminated sediment cores and top layer sediment were measured by gas-purging. Desorption from sediment was deduced to be triphasic:  fast, slowly, and very slo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
85
0

Year Published

2000
2000
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 106 publications
(95 citation statements)
references
References 45 publications
(49 reference statements)
10
85
0
Order By: Relevance
“…The extraction and clean-up (including recoveries) of the Tenax traps was described earlier [16]. The procedure for PAH extraction, clean-up, and analyses was as described earlier [16]. The PCBs were analyzed with a Hewlett-Packard (Amstelveen, The Netherlands) 5890 gas chromatography-electron capture detector as described previously [17].…”
Section: Extraction Clean-up and Chemical Analysesmentioning
confidence: 99%
“…The extraction and clean-up (including recoveries) of the Tenax traps was described earlier [16]. The procedure for PAH extraction, clean-up, and analyses was as described earlier [16]. The PCBs were analyzed with a Hewlett-Packard (Amstelveen, The Netherlands) 5890 gas chromatography-electron capture detector as described previously [17].…”
Section: Extraction Clean-up and Chemical Analysesmentioning
confidence: 99%
“…At the end of spiking, the sediment-naphthalene mixture was immediately used in the experiment with no significant post-mixing storage duration. It has been shown that sorption/desorption chemistry and bioavailability of the spiked compounds differ from those in the native contaminants (Alexander, 1995; Ten Hulscher et al, 1999), with higher mobility that would be advantageous considering the limited experimental durations.…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, the nonlabile, slowly desorbing fraction in sediment has recently been shown to be composed of two fractions (slow and very slow), resulting in triphasic desorption kinetics. The slow-and very slow-desorbing phases differ in their first order rate constants by about two orders of magnitude for chlorobenzenes, PCBs, and PAHs (Cornelissen et al, 2000, Kan et al, 2000Ten Hulscher et al, 1999). Equilibrium sorption of compounds at these two nonlabile, kinetically different sorption domains could be described by Langmuir isotherms, whereas the sorption of compounds at rapidly desorbing sites follows linear isotherms (Cornelissen et al, 2000).…”
Section: Fast and Slow Desorption Domainsmentioning
confidence: 99%